Control of antiferromagnetic domain distribution via polarization-dependent optical annealing - Takuya Higuchi (Nature Portfolio, 2016)
The control of magnetic domains in antiferromagnets is limited by the lack of a net magnetic moment which may be manipulated by external stimuli. Here, the authors present an optical method for switching such domain states in MnF2based on azimuth-dependent absorption of linearly polarized light.